Vulneración del principio constitucional a la prueba, en los procedimientos contravencionales de tránsito por estado de embriaguez, por parte de los agentes policiales al exigir que se realicen la prueba de alcoholemia. - Veintimilla Guanoquiza, Cristian Fernando (2023)
In Ecuador, the procedures handled by traffic agents with respect to accidents, are handled in most cases by pressuring the offenders to perform the alcohol test, otherwise it will be presumed that they are in the maximum degree of alcohol intake. , as determined by numeral 5 of article 464 of the COIP, which would not constitute evidence since there is pressure to do so, in such a way that it violates the right to due process in this type of procedure, since numeral 4 of the Constitution of Ecuador, stipulates that in the event of obtaining evidence acted in violation of the law, these will not have any validity and therefore will lack probative effectiveness, therefore it is important to legally analyze whether the norm that provides for the sanction for driving in state of drunkenness, and especially by refusing to perform the breathalyzer test violates due process in terms of probative effectiveness, it is an unconstitutional provision, which is violated by the Traffic Agents by demanding that the breathalyzer test be carried out supporting their request with what is determined in the COIP, that when presuming with the refusal to perform the breathalyzer test will be in the maximum degree of drunkenness, considering that several times it is sanctioned for a mere presumption, which causes the offender to perform the alcohol test somewhat forced, emphasizing that there are few judges who, by not having any proof, can declare the innocence of the sanctioned, therefore if the traffic judge when considering the alcohol test, as an evidentiary element in traffic violations, is violating constitutional law , the methodology used in the present investigation is the field one, which will allow working in the place and with the indicated actors and the descriptive one, which will help to describe the phenomena to be studied in all aspects.